Postnatal RBC arachidonic and docosahexaenoic acids deficiencies are associated with higher risk of neonatal morbidities and mortality in preterm infants. (November 2017) - Fares, S.; Sethom, M.M.; Hammami, M.B.; Cheour, M.; Feki, M.; Hadj-Taieb, S.; Kacem, S.
Abstract: Arachidonic (AA) and docosahexaenoic (DHA) acids are essential for the health and development of the neonate. Red blood cell (RBC) fatty acids were analyzed in 583 very low birth weight (VLBW) infants and 274 term infants using capillary gas chromatography. VLBW infants exhibited significantly lower RBC AA (13.0 ± 0.89 vs. 13.5 ± 0.98) and DHA (3.77 ± 0.60 vs. 3.80 ± 0.62), but higher n6:n3 ratio (3.97 ± 0.46 vs. 3.63 ± 0.37) than term infants. In VLBW infants, DHA was lower in those born with small for gestational age (3.69 ± 0.57 vs. 3.86 ± 0.58) and those who suffered from neonatal sepsis (3.73 ± 0.60 vs. 3.86 ± 0.55). Both AA and DHA were significantly lower in infants who developed respiratory distress syndrome or intraventricular hemorrhage, and those who died during the hospital stay. VLBW infants had lower postnatal RBC AA and DHA levels than term infants did. These deficits are associated with higher risk of neonatal morbidities and mortality. Highlights: Postnatal red blood cell (RBC) fatty acids profile in Tunisians preterm infants is reported. Preterm infants showed lower RBC AA and DHA, but higher n6:n3 ratio than term infants. Low RBC AA and DHA levels and high n6:n3 ratio are associated with higher risk for neonatal morbidity and mortality in VLBW infants.